2015
DOI: 10.1111/ahg.12111
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Polymerase γ Mutations and Their Implications in mtDNA Alterations in Colorectal Cancer

Abstract: SummaryMitochondrial DNA was found to be highly mutated in colorectal cancer cells. One of the key molecules involved in the maintenance of the mitochondrial genome is the nuclear-encoded polymerase gamma. The aim of our study was to determine if there is a link between polymorphisms within the polymerase gamma gene (POLG) and somatic mutations within the mitochondrial genome in cancer cells. We investigated POLG sequence variability in 50 colorectal cancer patients whose complete mitochondrial genome sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Nevertheless, the occurrence of such mutations may not have the same molecular background as the nuclear ones, as previous studies have shown lack of any association between the occurrence of mitochondrial and nuclear microsatellite instability (Venderbosch et al., ). It was previously proposed that polymerase gamma may be involved in mitochondrial length variation in D310 sequence in cancer (Skonieczna et al., ), but such associations were not observed for colorectal cancer patients (Linkowska et al., ). Thus, further studies are necessary to uncover molecular mechanisms underlying mitochondrial microsatellite instability in colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the occurrence of such mutations may not have the same molecular background as the nuclear ones, as previous studies have shown lack of any association between the occurrence of mitochondrial and nuclear microsatellite instability (Venderbosch et al., ). It was previously proposed that polymerase gamma may be involved in mitochondrial length variation in D310 sequence in cancer (Skonieczna et al., ), but such associations were not observed for colorectal cancer patients (Linkowska et al., ). Thus, further studies are necessary to uncover molecular mechanisms underlying mitochondrial microsatellite instability in colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In a study of 65 colorectal cancers, it has been suggested that hypomethylation of specific sites on CpG islands of the D-loop promoter may be involved in the regulation of mtDNA copy numbers [56]. Moreover, it has been reported that polymorphisms within the nuclear-encoded polymerase gamma gene (POLG), which codifies for a key component of the mitochondrial genome maintenance machinery, may lead to a decrease in mtDNA content and mitochondrial dysfunction [57]. Curiously, a homozygous polymorphic insertion (AluYb8MUTYH) in the 15th intron of the MUTYH base excision repair gene has been associated with a significant reduction of the type 1 MUTYH protein that localizes to mitochondria as well as lowered mtDNA content in age-related diseases [58].…”
Section: Mtdna Copy Number Alterationsmentioning
confidence: 99%
“…2 Nevertheless, our previous study excluded the possibility that somatic mtDNA mutations arose in CC cells as a result of POLG gene mutations. 3 Thus, it remains to be determined whether other genes involved in mtDNA repair are associated with the accumulation of somatic mtDNA mutations in CC cells.…”
Section: Introductionmentioning
confidence: 99%